Ribosomal protein L5 (RPL5)/ E2F transcription factor 1 (E2F1) signaling suppresses breast cancer progression via regulating endoplasmic reticulum stress and autophagy. Issue 4 (1st April 2022) - Ma, Xiaoping; Li, Yan; Zhao, Bing
ABSTRACT: Endoplasmic reticulum stress (ERS) is associated with breast cancer progression. However, the potential role of ribosomal protein L5 (RPL5) on ERS in breast cancer remains unclear. This study aimed to determine the role of RPL5/E2F transcription factor 1 (E2F1) in breast cancer. It was found that RPL5 was downregulated in breast cancer cells and tissues. Additionally, overexpression of RPL5 inhibited cell proliferation. Moreover, the levels of ERS and autophagy markers were estimated using western blotting. Overexpression of RPL5 induced ERS and suppressed autophagy. Additionally, RPL5 downregulated E2F1, which was overexpressed in breast cancer cells. However, E2F1 knockdown promoted the transcriptional activation of glucose regulated protein 78 (GRP78), suppressed ERS response, and promoted autophagy. Rescue assays indicated that the effects of RPL5 on ERS and autophagy were abolished by E2F1. Taken together, RPL5 inhibited the growth of breast cancer cells by modulating ERS and autophagy via the regulation of E2F1. These findings suggest that RPL5 has a tumor-suppressive effect in breast cancer. Graphical abstract: uf0001